Guaiane-Type Sesquiterpenoids from Fissistigma oldhamii Inhibit the Proliferation of Synoviocytes - Zhou, Xue-Ming; Zheng, Cai-Juan; Zhang, Yu-Qin; Zhang, Xiao-Peng; Song, Xiao-Ping; Xu, Wei; Chen, Guang-Ying (Planta Medica, 2017)
Three guaiane-type sesquiterpenoids, dysodensiols G–I (1–3), together with five known sesquiterpenoids (4–8) were isolated from the stems of Fissistigma oldhamii (Hemsl.) Merr. Compound 1 represents the first example of an ene(6 → 5)-abeo-14-norguaiane sesquiterpenoid derived from natural products. Their structures were elucidated by a combination of 1D and 2D NMR and MS spectra. The absolute configuration of 2 was determined by an X-ray crystallographic analysis. The inhibitory effect of all compounds on the proliferation of primary synovial cells was evaluated. Compound 3 showed a potent inhibitory effect on the proliferation of synoviocytes with an IC50 value of 1.0 µM.
Keywords: Annonaceae; Fissistigma oldhamii (Hemsl.) Merr; guaiane-type sesquiterpenoids; norisoprenoid; synoviocytes